SERUM METALLOPRETEINASE 3 (MMP-3) LEVELS IN LUNG CANCER AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE (COPD) PATIENTS - Soemarwoto, Retno Ariza; Mustofa, Syazili; Suwarno, Sukarti San; Yunus, Faisal; Listiandoko, Raden Dicky Wirawan; Sinaga, Fransisca TY; Febrihartati, Isura (Universitas Aisyah Pringsewu, 2025)
Chronic Obstructive Pulmonary Disease (COPD) and Lung Cancer are among the diseases with high mortality rates and a similar genetic disposition. COPD is known to be a significant risk factor for lung cancer. Matrix metalloproteinase-3 (MMP-3) is a protein that plays a role in the growth stage of cancer that has the potential to develop COPD into lung cancer. This descriptive observational study aimed to compare plasma MMP-3 levels among four groups: healthy individuals, lung cancer patients, COPD patients, and patients with both lung cancer and COPD. The findings revealed that plasma MMP-3 levels were lowest in the healthy group and higher in the other groups. The increase in plasma MMP-3 levels among pathological subjects suggests a potential association between serum MMP-3 levels and the development of lung cancer in COPD patients. However, further research is needed to clarify this relationship.